EVALUASI KEKUATAN CONCBLOCK DENGAN AGREGAT HALUS DAN AGREGAT KASAR DARI TEMPURUNG KELAPA - Agnes Yuanita Bintoro; Arthur Daniel Limantara; Sigit Winarto (Kadiri University, 2018)
The growing era of the use of production waste can be processed into environmentally friendly materials. Therefore, by utilizing coconut shell waste for a concrete block mixture. The purpose of this study was to determine the compressive strength of the concrete from the addition of a mixture of fine aggregate and coarse aggregate from coconut shells. Concrete samples were tested at 28 days of concrete. For each variation is Variation 0% obtained a compressive strength of 18.5 MPa and absorption of concrete of 13.60%. The variation of 20% coconut shell and 15% shell powder obtained a compressive strength of 11.4 MPa and concrete absorption capacity of 11.69%. A variation of 25% coconut shell and 20% shell powder obtained a compressive strength of 7.6 MPa and concrete absorption capacity of 11.64%. A variation of 30% coconut shell and 25% shell powder obtained a compressive strength of 6.7 MPa and concrete absorption capacity of 10.17%. From these results, it can be seen that the concrete given a mixture of fine aggregate and coarse aggregate from coconut shell has decreased compressive strength and absorption capacity from normal concrete yields.Semakin berkembangnya zaman pemanfaatan limbah hasil produksi dapat diolah menjadi bahan yang ramah lingkungan. Oleh karena itu dengan memanfaatkan limbah tempurung kelapa untuk bahan campuran concblock. Tujuan dari penelitian ini untuk mengetahui kuat tekan beton dari penambahan campuran agregat halus dan agregat kasar dari tempurung kelapa. Sampel beton diuji pada umur beton 28 hari. Untuk setiap variasi adalah : Variasi 0% diperoleh kuat tekan sebesar 18,5 Mpa dan daya serap beton sebesar 13,60%. Variasi 20% tempurung kelapa dan 15% serbuk tempurung diperoleh kuat tekan sebesar 11,4 MPa dan daya serap beton sebesar 11,69%. Variasi 25% tempurung kelapa dan 20% serbuk tempurung diperoleh kuat tekan sebesar 7,6 MPa dan daya serap beton sebesar 11,64%. Variasi 30% tempurung kelapa dan 25% serbuk tempurung diperoleh kuat tekan sebesar 6,7 Mpa dan daya serap beton sebesar 10,17%. Dari hasil tersebut dapat diketahui bahwa beton yang diberi campuran agregat halus dan agregat kasar dari tempurung kelapa mengalami penurunan kuat tekan dan daya serap dari hasil beton normalnya.